MIS-C Treatment: Is IVIG Always Necessary? - Licciardi, Francesco; Baldini, Letizia; Dellepiane, Marta; Covizzi, Carlotta; Mogni, Roberta; Pruccoli, Giulia; Orsi, Cecilia; Rabbone, Ivana; Parodi, Emilia; Mignone, Federica; Montin, Davide (Frontiers in Pediatrics, 2021)
MIS-C is a severe inflammatory syndrome associated with SARS-CoV-2 exposure. Intravenous immunoglobulin (IVIG) is considered the first-tier therapy, but it implies infusion of large fluid volumes that may worsen cardiac function. Since April 2020 we have developed a treatment protocol designed for decreasing the need of IVIG in the early phase of MIS-C. In the last year, 31 patients have been treated with this protocol: 25 with high dose pulse methylprednisolone (MP, 10 mg/Kg) and 6 with 2mg/Kg. 67.7% of the patients responded to the initial treatment, the others needed a step-up either with Anakinra (25.8%) or MP dose increase (6.5%). IVIG treatment was added in 4 patients. In our cohort only 1 patient (3.2%) needed ICU admission or inotropic support, 1 patient developed a small coronary artery aneurysm (3.2%). Timely start of MP therapy and careful fluid management might improve the outcomes in MIS-C.